12. Survival outcomes of hepatectomy for hepatocellular carcinoma using LigaSure and Kelly forceps for parenchymal excision combined Glissonean pedicle approach: A retrospective single-centre study - Son, Tran Que; Hung, Tran Manh; Hoc, Tran Hieu; Truong, Trieu Van; Thang, Nguyen Toan; Tuyen, Pham Van; Thanh, Nguyen Tuan; Dinh, Ngo Quang; Hue, Bui Thị Minh; Minh, Nguyen Van; Kien, Cu Trung; Kien, Nguyen Trung; et al. (Tạp chí Nghiên cứu Y học, 2023)
Standard procedures in hepatectomy for hepatocellular carcinoma (HCC) include selective pedicle control and anatomical liver resection. We provide our experience using LigaSureTM and Kelly forceps for parenchymal excision combined with the Glissonian pedicle approach for HCC patients. Sixty-seven patients underwent hepatectomy between June 1st 2016 and May 30th 2020. Prospectively gathered data on surgical outcomes and long-term survival results are given. Minor liver resections comprise 85% of all surgical procedures. The median operative time was 132.1 minutes (range, 102 to 195 mins), and the median intraoperative estimated blood loss was 210 ± 158 (range, 150 – 750) mL. The rate of morbidity was 17.9%, including pleural effusion (13,4%), biliary fistula (0%), liver failure (1.5%), and intra-abdominal bleeding (1.5%). The mean overall survival time by Kaplan – Meier method is 33 ± 0.6 months. The rate of overall survival after 1, 2, and 3 years was 95.5%, 84.5% and 79.4%, respectively. The mean disease-free survival (DFS) time was 25.9 ± 2.1 (months). The recurrence rates after 3 months, 6 months, 12 months, and 24 months were 9.6%, 12.4%, 30.5%, and 42.6%, respectively. Conclusion: In a nation with minimal assets, the Glissonian pedicle approach with the Ligasure and Kelly forceps is a safe and successful method for performing hepatectomy. It permits an anatomical excision with minor morbidity when operated by experienced surgeons.